Cubos gráficos OLAP - -Compilación CEO, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
Abstract. An OLAP (Online analytical processing) cube is a data structure that allows fast analysis of data. It can also be defined as the capability of manipulating and analyzing data from multiple perspectives. The arrangement of data into cubes overcomes a limitation of relational databases. Relational databases are not well suited for near instantaneous analysis and display of large amounts of data. Instead, they are better suited for creating records from a series of transactions known as OLTP or On-Line Transaction Processing. Although many report-writing tools exist for relational databases, these are slow when the whole database must be summarized. Resumen. Un cubo OLAP, OnLine Analytical Processing o procesamiento Analítico en Línea, término acuñado por Edgar Frank Codd de EF Codd & Associates, encargado por Arbor Software (en la actualidad Hyperion Solutions), es una base de datos multidimensional, en la cual el almacenamiento físico de los datos se realiza en un vector multidimensional. Los cubos OLAP se pueden considerar como una ampliación de las dos dimensiones de una hoja de cálculo.